John F. Kennedy and the Politics of Faith - Lacroix, Patrick (Book collections on Project MUSE., 2021)
"The public conversation on religion and politics has focused on the dominance of evangelicals and the Religious Right, which historians trace to the divisive political issues of the late 1960s and early 1970s. Patrick Lacroix traces present-day religious activism to an earlier moment: the administration of John F. Kennedy, the nation's first Catholic president. Scholars frequently mention the 1960 election as a blow to anti-Catholicism and a sign that Americans accepted the idea of a Catholic president, but as Lacroix shows, the "religious issue" of 1960-Kennedy's Catholic faith-was not laid to rest with the Democratic hopeful's victory. Religious hopes and fears were rechanneled, sometimes in unexpected ways. As Kennedy staunchly defended church-state separation, he incurred the wrath of fellow Catholics. Mainline Protestants, by contrast, buried the hatchet and became the president's most faithful supporters. Quickly, through civil rights campaigns, US engagement in Vietnam, and the Second Vatican Council, new alliances formed. As he embraced racial justice and signed a nuclear test ban treaty in 1963, Kennedy assembled an ecumenical, liberal coalition that we now know as the Religious Left. As important as the campaign of 1960 was, the full story of religion and politics during the Kennedy administration has been lost. The reason for the oversight is plain: through much of his administration, Kennedy thought religion to be a distraction. His religious upbringing seldom influenced his policy decisions, and he left few written statements regarding his own values and beliefs. Even so, religious activists appealed to Kennedy throughout his years in office, and the president responded and adapted, albeit grudgingly. John F. Kennedy and the Politics of Faith reveals the larger picture of faith and American politics during this critical moment in history, shedding light not only on liberal ecumenical activism but also the conservative response that flourished in later years"--